Violencia paraestatal y organizaciones de derecha. Aportes para repensar el entramado represivo en la Argentina, 1970-1976 - Juan Luis Besoky (Nuevo mundo - Mundos Nuevos, 2016)
In this paper I analyze the concepts of ‘parastatal’, ‘paramilitary’ and ‘vigilante’ (parapolice) according have been used in the literature. In the second part I focus on the analysis of the para-statal repressive violence in Argentina between 1973 and 1975 with special emphasis on the "Triple A" (“Anti-Communist Alliance Argentina"). Finally I analyze to what extent and in what ways the theoretical concepts can serve to classify paramilitary violence occurred in Argentina.